Accelerating the research, development, and acquisition of medical countermeasures against biological warfare agents : interim report (The National Academies Press, 2003)
Having the means to protect its military personnel against biological warfare agents is a long-standing objective for the United States. The development of safe and effective medical countermeasures -- vaccines, antitoxins, and prophylactic and therapeutic drugs -- against those agents is one of the essential components of the nation's biological defense efforts. Currently, the United States has a limited repertoire of licensed medical countermeasures that the Department of Defense (DoD) can use to protect members of the armed forces against more than a dozen bacteria, viruses, and toxins identified as possible biological warfare agents. As part of its Chemical and Biological Defense Program, DoD is engaged in research and development efforts aimed at making available a broader range of medical countermeasures.